(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of dental caries and associated factors among patients attending the Peshawar Dental College and Hospital. Study Design: Hospital-based cross-sectional study Place and Duration of Study: This study was conducted at the Department of Operative Dentistry and Endodontic of Peshawar Dental College and Hospital during the study period from September 2023 to December 2023. Methods: A total of one hundred & thirty-six patients meeting inclusion criteria utilizing a convenient sampling method were recruited for the study. Data collection was carried out using structured questionnaires and clinical examinations. Clinical examination was performed by cleaning and drying the teeth and using a mouth mirror with adequate light and a ball-end Community Periodontal Index (CPI) probe. Dental caries were identified when a lesion was observed in the pit or fissure, or on a smooth surface, characterized by a detectable soft floor, undermined enamel, soft wall, or temporary restoration. The Chi-square test was employed with a significance level of P ≤ 0.05 to assess potential associations of categorical variables. Results: The frequency of dental caries among patients was found to be 85% with varying degrees of severity. The mean age of the participants was 33 ± 12.66 years and ranged from 13 to 80 years. Aspects including age, oral hygiene routines, dietary patterns, and socioeconomic status displayed significant association with the presence of dental caries (p < 0.05). Poor oral hygiene practices and frequent use of sugary meals were the most major risk factors. Conclusion: Dental caries frequency was notably influenced by factors such as oral hygiene status, level of education, and income level. Patients with poor oral hygiene, lower educational levels, and lower income were identified as having at heightened susceptibility to caries